Pengaruh Work Life Balance dan Lingkungan Kerja terhadap Kinerja Pegawai Dimediasi Kepuasan Kerja pada Sekretariat Daerah Kabupaten Batang - Diputra, Fadila Kusuma; Rijanti, Tristiana (Universitas Syiah Kuala, 2025)
This study aims to examine and analyze the influence of work-life balance and work environment on employee performance mediated by job satisfaction at the Batang Regency Secretariat. Data collection was conducted by distributing questionnaires to 109 respondents from a total population of 189 respondents. The collected data were analyzed using factor analysis to test validity, reliability testing using Cronbach's Alpha, hypothesis testing using multiple linear regression with the Statistical Package for Social Sciences Version 27 application, and mediation testing using the Sobel Test. The results of the study indicate that (1) work-life balance has a positive and significant effect on job satisfaction, (2) the work environment has a positive and significant effect on job satisfaction, (3) work-life balance has a positive and significant effect on employee performance, (4) work environment has a positive and significant effect on employee performance (5) job satisfaction has a positive and significant effect on employee performance (6) job satisfaction mediates work-life balance on employee performance (7) job satisfaction mediates work environment on employee performance.